Advanced instantaneous shifted‐excitation Raman difference spectroscopy (iSERDS) using a laser pointer. (9th December 2015) - Grüber, Klaas; Kiefer, Johannes
Abstract : Shifted‐excitation Raman difference spectroscopy (SERDS) is an established experimental method for obtaining Raman spectra from fluorescing samples. However, great care must be taken when the experiment is carried out. Some experimental parameters such as the intensity and the wavelength shift are very sensitive, and small inaccuracies in the settings can result in significant artifacts in the reconstructed Raman spectrum. Instantaneous shifted‐excitation Raman difference spectroscopy (iSERDS) using a broadband light source provides a certain flexibility regarding the parameter settings because there are multiple pairs of shifted wavelength spectra recorded simultaneously. The present work demonstrates the first experimental implementation of iSERDS using a commercial laser pointer as a moderately broadband excitation source. Employing a transmission grating for spatially dispersing the laser radiation in the measurement volume simplifies the experiment significantly compared with the previous iSERDS method that employs two reflection gratings for this purpose. Moreover, an evaluation strategy is developed based on a systematic investigation of the influence the main experimental parameters (i.e. the wavelength shift, the intensity, and noise) have on the SERDS spectrum and on the derived Raman spectrum. Recommendations on the optimal choice of settings in iSERDS and conventional SERDS experiments are made. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : An advanced approach for instantaneous shifted‐excitation Raman difference spectroscopy is demonstrated utilizing a commercial laser pointer as light source. The moderately broadband radiation is spatially dispersed inside the object of investigation. The generated scattering signal is imaged onto the slit of an imaging spectrograph. The individual pixel lines on the detector represent Raman spectra with slightly shifted‐excitation wavelength and hence allow shifted‐excitation Raman difference spectroscopy spectra to be derived. A computational analysis of the experimental parameters reveals optimized settings.